BIM for Building Owners and Developers. - Reddy, K. Pramod (John Wiley & Sons, 2011)
This is the first book written for building owners and developers about Building Information Modeling.€ Making the business case for owners' use of BIM, the book helps owners align the use of BIM to their real business objectives through strategic planning, SWOT and GAP analysis excercice. Written by the President of RCMS, and based on his ongoing series of BIM Bootcamps he's presented to over 1,200 owners and developers nationwide over the past year, the book presents real-world, practical guidance on effectively using BIM to improve business processes.